2022
DOI: 10.3389/fimmu.2022.859419
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Management of Primary Membranous Nephropathy and Rituximab-Refractory Membranous Nephropathy

Abstract: Primary membranous nephropathy (pMN) is an auto-immune disease characterized by auto-antibodies targeting podocyte antigens resulting in activation of complement and damage to the glomerular basement membrane. pMN is the most common cause of nephrotic syndrome in adults without diabetes. Despite a very heterogeneous course of the disease, the treatment of pMN has for many years been based on uniform management of all patients regardless of the severity of the disease. The identification of prognostic markers h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 118 publications
(193 reference statements)
1
27
0
4
Order By: Relevance
“…Therefore, effective and safe therapeutic strategies for refractory IMN must be explored. In the past decade, significant advances in understanding of IMN have established that it is an autoantibody-driven disease[ 21 , 22 ]. As a result, there is a clear choice for treating B-cell depletion.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, effective and safe therapeutic strategies for refractory IMN must be explored. In the past decade, significant advances in understanding of IMN have established that it is an autoantibody-driven disease[ 21 , 22 ]. As a result, there is a clear choice for treating B-cell depletion.…”
Section: Discussionmentioning
confidence: 99%
“…Except for the above factors, there are several factors including serum RTX levels, the existence of anti- RTX antibodies, Th17-mediated inflammation and so on that have been demonstrated to influence the efficacy of RTX in the treatment of membranous nephropathy ( Teisseyre et al, 2022 ). Studies have confirmed that low RTX levels at month 3 correlate with poor B-cell depletion at months 3 and 6, with high anti-PLA2R antibody titer at months 3, 6 and 12, and with proteinuria at months 3, 6 and 12.…”
Section: Discussionmentioning
confidence: 99%
“…Nanoparticles with autoimmune disease-relevant peptides bound to major histocompatibility complex class II molecules could also be used to induce antigen-specific Tregs that promote the differentiation of B-cells into disease-suppressing regulatory B-cells 192 . Whether these new biotechnologies may have a role in the treatment of refractory PMN is therefore worth investigating 193 .…”
Section: Depleting Autoreactive B-cells and Inducing Immunotolerancementioning
confidence: 99%